Neoliberalism, Education and Citizenship Rights of Unemployed Youth in Post-Apartheid South Africa - Swanson, Dalene M. (2013)
Via the evocation of two personal narratives of lived experiences of/with youth in South Africa, the paper addresses issues relating to youth, unemployment, education and structural injustice. These narrative vignettes reflect events of injustice that occur within the human sphere and fall within the interstices between competing discourses as sites of struggle for meaning and supremacy. It is here where the lived effects of unjust political structures can be witnessed as violent assaults on individual and collective bodies, psyches and souls, while the indomitability of the human spirit rallies to rise above such adversity. Both experiences, while specific, nevertheless articulate a difficult ‘glocalising’ relationship with ‘the general’ and ‘universal’ in the global interconnectedness of injustice and the effects of a dehumanising ideology. They are underscored by a historical legacy of apartheid and authoritarianism, but advanced through a newer discourse of neoliberal, globalising modernism. Both ideologies converge in untroubled alignment through similarly operational codes of control and the endemic forms and frames of (in)difference. The paper argues that racialised unemployed youth in South Africa carry the burden of structural political dysfunctionality and state ineptitude, and they are pathologised and differentially constructed as ‘failed’ citizens as a consequence. Not only are South African youth expected to carry the burden of unemployment, but also the flag of the nation’s political transformation as well, in a context of contradiction and maladministration overlaid by the debilitating effects of neoliberal governmentality. Youth identity is framed in nationalist economic terms, justified and advanced through the contemporary, global, modernist condition, supported by neoliberal capitalist relations. The historical, embodied and material injustices shape what is possible for youth, specifically unemployed youth, in South Africa today.